Area-selective epoxy coatings by DBD-PECVD in 3D cavities for protein coupling. Issue 4 (6th October 2015) - Herrmann, Annika; Lachmann, Kristina; Fischer, Lisa; Kovac, Janez; Thomas, Michael
Abstract : Biofunctional coatings containing epoxy groups coatings were deposited on selective areas on the inner surfaces of three-dimensional (3D) cavities using a chemical vapor deposition process activated by a dielectric barrier discharge. The binding capacity of plasma polymers to proteins was analyzed. The chemical functionalization was carried out using glycidyl methacrylate as a precursor. Thin coatings with a high density of epoxy groups were achieved which form the basis to bind proteins. Using a specially developed electrode, geometry coatings were deposited in the form of four parallel rectangular bands of identical dimensions along the inner surface of a polypropylene syringe. The chemical composition was analyzed by attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy. To prove the reactivity of the coatings, these were exposed to hydrochloric acid vapors which cause an opening of the ring of the epoxy group. Resulting OH groups were also determined by the ATR-FTIR measurements. For evaluation, samples were incubated in bovine serum albumin solution and afterward colored by Coomassie Brilliant Blue G-250. Proteins, immobilized on the coating, were detected by an immunoglobulin G antibody coupled with horseradish peroxidase. Visualization was performed by using 3, 3′, 5, 5′-tetramethylbenzidine solution. The results show a great potential of atmospheric-pressure plasma processes for generating chemically reactive area-selective coatings on 3D substrates to achieve a coupling of biomolecules to polymer surfaces.